Consumers' perception and acceptance of boiled and fermented sausages from strongly boar tainted meat. (August 2016) - Meier-Dinkel, Lisa; Gertheiss, Jan; Schnäckel, Wolfram; Mörlein, Daniel
Abstract: Characteristic off-flavours may occur in uncastrated male pigs depending on the accumulation of androstenone and skatole. Feasible processing of strongly tainted carcasses is challenging but gains in importance due to the European ban on piglet castration in 2018. This paper investigates consumers' acceptability of two sausage types: (a) emulsion-type (BOILED) and (b) smoked raw-fermented (FERM). Liking (9 point scales) and flavour perception (check-all-that-apply with both, typical and negatively connoted sensory terms) were evaluated by 120 consumers (within-subject design). Proportion of tainted boar meat (0, 50, 100%) affected overall liking of BOILED, F (2, 238) = 23.22, P < .001, but not of FERM sausages, F (2, 238) = 0.89, P = .414. Consumers described the flavour of BOILED-100 as strong and sweaty. In conclusion, FERM products seem promising for processing of tainted carcasses whereas formulations must be optimized for BOILED in order to eliminate perceptible off-flavours. Boar taint rejection thresholds may be higher for processed than those suggested for unprocessed meat cuts. Highlights: Boiled and fermented sausages with varying levels of tainted boar meat were made. Consumer acceptance and perception were evaluated in a CLT. No impaired liking was observed for fermented products. Formulations must be optimized for boiled sausages made from tainted boar meat.